Franz Brentano und sein philosophischer Nachlass - Binder, Thomas (TEXTOLOGIE, 2019)
Although Franz Brentano was one of the most influential turn-of-the-century philosophers, he, like Ludwig Wittgenstein, published little but left a large philosophical legacy. This study examines the biographical and theoretical reasons for Brentano's reluctance to publish and offers an overview of the checkered history of his philosophical legacy.